Global Jihadism and Organizational Complexity in Social Movements - Streiter, Andreas (Momentum Quarterly, 2018)
This article illustrates the “rhizome” metaphor of Gilles Deleuze and Félix Guattari with the example of global jihadism. The aim of the article is twofold: frst, it shows the potential of the metaphor to contribute to a better understanding of dynamic modalities of organizing. Second, it contributes to a more comprehensive understanding of global jihadism as an empirical phenomenon. By implementing the rhizome metaphor, it becomes apparent that the organization of global jihadism extends beyond an either/or duality of hierarchy and network, but that it is an organizational multiplicity which comprises both hierarchical and network dimensions at the same time. The extent of those dimensions is constantly changing.
Keywords: Organization; Rhizome; Jihadism; al-Qaeda; IS